Coronary Sinus Mapping through a Persistent Left Superior Vena Cava in Wolff-Parkinson-White Syndrome - Perin, Emerson (1991)
Persistent left superior vena cava is not an uncommon finding in patients undergoing evaluation for preexcitation syndromes. In such patients, this anatomical configuration might be used advantageously for mapping and ablation of a left-sided accessory pathway during electrophysiologic studies. We successfully used this mapping approach in a 16-year-old boy undergoing evaluation for Wolff-Parkinson-White syndrome. The patient was found to have a persistent left superior vena cava confluent with the coronary sinus. During electrophysiologic studies, mapping of the left-sided accessory pathway was facilitated by retrograde entry into the coronary sinus through the persistent left superior vena cava. Mapping was also performed in the conventional manner, yielding identical results and thus validating this new technique. (Texas Heart Institute Journal 1991;18:122-3)